Perfect little children [compact disc, unabridged] - Hannah, Sophie, 1971- (Harper Audio, 2020)
All Beth has to do is drive her son to his soccer game, watch him play, and then return home. Just because she knows her ex-best friend lives near the field, that doesn't mean she has to drive past her house and try to catch a glimpse of her. Why would Beth do that and risk dredging up painful memories? She hasn't seen Flora for twelve years. She doesn't want to see her today, or ever again. But she can't resist. She parks outside the open gates of Newnham House, watches from across the road as Flora arrives and calls to her children Thomas and Emily to get out of the car. Except, there's something terribly wrong. Flora looks the same, only older. Twelve years ago, Thomas and Emily were five and three years old. Today, they look precisely as they did then. They are Thomas and Emily without a doubt, but they haven't changed at all. They are no taller, no older. Why haven't they grown? How is it possible that they haven't grown up?